EDIBLE FILM BERBASIS PULP KAKAO (Theobroma cacao L.) DAN KULIT BUAH SEMANGKA (Citrullus lanatus) SEBAGAI TEKNOLOGI FOOD PACKAGING - Reski, Alpi Meitia; Patricia, Anggun Dwi; Azira, Ayu; Sihotang, Andreas; Tarigan, Indra Lasmana (Tanjungpura University, 2024)
This study evaluated the physical characteristics (thickness and surface morphology) and chemical properties (composition and functional groups) of edible films made from cocoa pulp and watermelon rind. Additionally, it investigated the effect of citrulline concentration on the solubility of the film and its impact on extending the shelf life of Jambi potato dodol. The experimental data were statistically analyzed using analysis of variance (ANOVA) to determine the significance of differences among treatments. The citrulline concentration variation factor consisted of two concentration levels, namely 5% and 15%. The results showed that the thickness of the edible film was 0.26 mm for the film containing 5% citrulline and 0.16 mm for the film with 15% citrulline. The viscosity of the film-forming solution influenced the surface morphology of the edible film. A chemical characteristics test was carried out using FTIR analysis, which showed the presence of several different functional groups at various wave numbers. Dodol packaged with edible film demonstrated a relatively good shelf life against microbial growth. The most effective edible film in enhancing resistance to bacterial contamination was the one containing 15% citrullin.